Conduction properties study on alginate incorporated with glycolic acid based solid biopolymer electrolytes - Ahmad Faizrin, Ahmad Fuzlin; Izan Izwan, Misnon; Ahmad Salihin, Samsudin (Trans Tech Publications, 2020)
This present work focuses on the conduction properties investigation on solid biopolymer electrolytes (SBEs) based alginate doped with various composition of glycolic acid (GA). The film was successfully prepared via solution casting technique and was characterized for conduction properties by using impedance spectroscopy. Based on ionic conductivity study, sample containing with 20 wt. % of GA possessed an optimum ionic conductivity of 5.32 × 10-5 Scm−1 at ambient temperature (303 K). The dielectric analysis revealed the highest ionic conductivity sample based alginate-GA SBEs has the highest dielectric constant and loss and increased significantly when temperature increases at ambient temperature. The dielectric properties shows that the entire alginate-GA SBEs are non-Debye behavior where there is no single relaxation occurred in the present system.